Versatile Mode-Locked Operations in an Er-Doped Fiber Laser with a Film-Type Indium Tin Oxide Saturable Absorber - Guo, Quanxin (Nanomaterials (Basel), 2019)
We demonstrate the generation of versatile mode-locked operations in an Er-doped fiber laser with an indium tin oxide (ITO) saturable absorber (SA). As an epsilon-near-zero material, ITO has been only used to fashion a mode-locked fiber laser as an ITO nanoparticle-polyvinyl alcohol SA. However, this type of SA cannot work at high power or ensure that the SA materials can be transmitted by the light. Thus, we covered the end face of a fiber with a uniform ITO film using the radio frequency magnetron sputtering technology to fabricate a novel ITO SA. Using this new type of SA, single-wavelength pulses, dual-wavelength pulses, and triple-wavelength multi-pulses were achieved easily. The pulse durations of these mode-locked operations were 1.67, 6.91, and 1 ns, respectively. At the dual-wavelength mode-locked state, the fiber laser could achieve an output power of 2.91 mW and a pulse energy of 1.48 nJ. This study reveals that such a proposed film-type ITO SA has excellent nonlinear absorption properties, which can promote the application of ITO film for ultrafast photonics.